Summerhill “dialogues” with the Viva Olho do Tempo School and de Griô Pedagogy - Sobreira, Antonio (Revista Hipótese, 2018)
This paper presents the pedagogical proposals of Summerhill School (Leiston, England, 1930) and the Escola Viva Olho do Tempo (Joao Pessoa Paraiba, 2004). Both experiences are guidedby happiness and non-compulsory education for children and youth revealing the amplitude of democratic schools in different socio-cultural realities.
Keywords: Complexity; School education; Summerhill; Freedom